IN VIVO HEPATOPROTECTIVE EFFECT OF CAFFEIC ACID ON MERCURIC CHLORIDE-INDUCED BIOCHEMICAL CHANGES IN ALBINO WISTAR RATS - MANOGARAN MANJU; GANESAN JAGASEESAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Mercury (Hg) is a highly dangerous and also one of the harmful heavy metals which induces oxidative stress in the animal body. The present study is planned to examine the possible defensive result of caffeic acid (CA) against mercury chloride (HgCl2)-induced hepatotoxicity in male albino Wistar rats, Rattus norvegicus. Methods: Sublethal dose of HgCl2 (1.29 mg/kg body weight) was administrated in rats for 15 days through oral dose and the CA was administrated for another 15 days on mercuric-intoxicated rats. After completing the scheduled exposure time, the rats were sacrificed and the whole liver organ was removed immediately from the animal, and it was used to carry out for biochemical and bioenzymological studies to observe. Results: The level of lipid peroxidation (LPO) content reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in the liver tissue. CA is an energetic component in the phenolic propolis extract and also in a wide variety of plants, and a strong antioxidant helps to prevent oxidative damage and to reduce oxidative stress. The antioxidants such as GPx, CAT, and SOD and non-antioxidant GSH were significantly decreased, and also, the LPO level was increased in mercury toxicity rats. The treatment of CA (5 mg/kg body weight) in the liver tissue shows considerable declining in the level of oxidant content and along with an increase in the level of antioxidant properties by the way of improvement in liver tissues. Antioxidant and non-antioxidant enzyme (LOP, GSH, GPx, SOD, and CAT) activities were also significantly decreased to near untreated control level when compared to Hg-treated group. The CA acid alone treatment showed the enhanced antioxidant levels and not any alteration in the levels of biochemical parameters when compared with control. Conclusion: These observations of the present experimental study clearly explained the detoxify effects and protective effect of CA against HgCl2 toxicity in liver tissue.